Geotechnical review of stope design for the sf3 orebody at Rosh Pinah Zinc Mine - Shali, George Peingondjambi (My University, 2022)
Rosh Pinah Zinc underground mine is located in the south of Namibia, 18 km from the Orange River and 100 km from the town of Oranjemund. The zinc-lead deposit is extracted via the open stoping mining method. The stability of open stopes was analysed with empirical and numerical modelling. The application of the stability graph method proposed by Potvin was used to analyse the stability of stope surfaces. Care was taken concerning the limitations of the stability graph method, which does not take into account the stress orientation relative to the stoping method. Furthermore, the stability graph does not consider the blasting effects occurring during stope blasting as well as in the vicinity around the stoping area. This project explores the impact of using a non-linear Improved Unified Constitutive Model (IUCM) using FLAC3D, which can provide estimates of the amount of over break to be expected as well as using traditional empirical stability methods to predict dilution. Over break in numerical modelling was interpreted using both the principal stresses and volumetric strain to forecast the expected level of dilution during the mining process using the numerical method. Furthermore, dilution using empirical methods was estimated using the equivalent linear overbreak slough. The results from numerical modelling indicated that the upper mined out stopes were stable and no major dilution was envisaged, and this was proved by use of the Cavity Monitoring System for mined out levels of 230 and 200. Furthermore, it was found that both empirical models and numerical modelling indicated a large amount of dilution to be expected as mining progresses downwards from Level 050 to Level -040 – owing to an increase in size of the stopes.
A thesis submitted in partial fulfilment of the requirements for Master of Science in Engineering to the Faculty of Engineering and Built Environment, School of Mining Engineering, University of the Witwatersrand, Johannesburg, 2021